Cognition and Rehabilitative Treatment of Upper Extremity Lymphedema after Radical Mastectomy - Jie JIA (康复学报)
Lymphedema is one of the most common complications after mastectomy. We paid much attention to it because lymphedema would impact negatively to physical and mental health of patients. The aim of this article is to discuss the current situation of the rehabilitation of breast cancer in China, and how well patients know about lymphedema, the treatment process of lymphedema and the mechanism of upper limb lymphedema. We also try to explore a standardized diagnosis and therapeutic pattern of upper limb lymphedema after radical mastectomy.